1997
DOI: 10.1007/s004420050346
|View full text |Cite
|
Sign up to set email alerts
|

The colonization of native phytophagous insects in North America by exotic parasitoids

Abstract: Classical biological control could have a major environmental cost if introduced natural enemies colonize and disrupt native systems. Although quantifying these impacts is difficult for systems already colonized by natural enemies, the a priori condition for such impacts can be evaluated based on the extent to which exotics have acquired native hosts. We use native host records for exotic parasitoids introduced into North America for biological control to document the number of exotic species that have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(35 citation statements)
references
References 26 publications
(28 reference statements)
0
35
0
Order By: Relevance
“…Environmental safety is an important issue for biological control (Andres 1985;Turner 1985;Pemberton 1985aPemberton , 1985bPemberton , 1995Pemberton , 1996Funasaki et al 1988;Howarth 1991;Miller and Applet 1993;Lockwood 1993aLockwood , 1993bCarruthers and Onsager 1993;Center 1995;McEvoy 1996;Simberloff and Stiling 1996;Morohasy 1996;Onstad and McManus 1996;Hawkins and Marino 1997;Louda et al 1997;Strong 1997; Thomas and Willis 1998;Strong and Pemberton 2000). There is now evidence of harm to a few non-target, native species caused by insects and other organisms imported to suppress pests, but a general assessment of the kinds and degrees of risk to native organisms owing to biological control is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental safety is an important issue for biological control (Andres 1985;Turner 1985;Pemberton 1985aPemberton , 1985bPemberton , 1995Pemberton , 1996Funasaki et al 1988;Howarth 1991;Miller and Applet 1993;Lockwood 1993aLockwood , 1993bCarruthers and Onsager 1993;Center 1995;McEvoy 1996;Simberloff and Stiling 1996;Morohasy 1996;Onstad and McManus 1996;Hawkins and Marino 1997;Louda et al 1997;Strong 1997; Thomas and Willis 1998;Strong and Pemberton 2000). There is now evidence of harm to a few non-target, native species caused by insects and other organisms imported to suppress pests, but a general assessment of the kinds and degrees of risk to native organisms owing to biological control is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Papers that followed, about nontarget impacts (Samways 1988;Howarth 1991;Simberloff and Stiling 1996;Hawkins and Marino 1997) began a debate that intensified after publication of widely read and discussed papers on impacts of introduced weevils on native thistles in the North American Great Plains (Louda et al 1997) and parasitic flies introduced against gypsy moth that also attacked native silkworms (Boettner et al 2000). Many entomologists debated the beneficial versus detrimental aspects of classical biological control in the late 1990s and early 2000s (see Follett and Duan 2000;Samways 1997;Lockwood et al 2001;Wajnberg et al 2001;Louda et al 2003;Pearson and Callaway 2003;Messing and Wright 2006).…”
Section: Controversy Regarding Environmental Safety Of Biological Conmentioning
confidence: 99%
“…This is especially true for predators and parasitoids that were released before approximately 1950, when impacts on nontarget species and communities were not a central concern and governmental oversight about the safety of releases had not been well established. For example, Hawkins and Marino (1997) reported that 16% of the 313 parasitoids of holometabolous hosts introduced into North America were found to parasitize nontarget hosts on occasion. In a more regional analysis, a 1988 survey of classical biological control introductions to Hawaii found that 22% of 243 classical biological control agents had been reported attacking nontarget hosts (Funasaki et al 1988).…”
Section: Direct Effectsmentioning
confidence: 99%
“…vVhile a lack of taxonomic knowledge of most parasitoid groups hinders the resolution of the data (Memmott, 1999), we do know that scores of introduced parasitoid species attack native insects (Hawkins and Marino, 1997). Although non-target effects are poorly known, parasitoids introduced long ago can harm native herbivore populations today (Boettner et al, 2000).…”
Section: Parasitoids and General Predatorsmentioning
confidence: 99%